Development of Electronic Books with Inquiry-Based Learning (5E) on Europe Continent in Social Studies for Mathayomsuksa 2 students - Puwanat, Sukanya; Busayanon, Kanrawee (Suan Dusit Graduate School Academic Journal, 2025)
The objectives of this research were: (1) To compare students’ learning achievement before and after of Mathayomsuksa 2 students who study using electronic books together with the inquiry-based learning process (5E) on the subject of Europe, Social Studies subject. (2) To study the satisfaction of Mathayomsuksa 2 students who study using electronic books together with inquiry-based learning (5E) on the subject of Europe, Social Studies subject. The sample comprised 30 Mathayomsuksa 2 students from Matthayom Ban Bang Kapi School in the second semester of the academic year 2023, Selected by purposive Selection. The research instruments included (1) Inquiry-based learning plan on the topic of Europe. (2) E-book on Europe, Social Studies subject. (3) Academic achievement test About Europe. (4) Satisfaction assessment with learning management using electronic books combined with inquiry-based learning (5E) Statistics used in data analysis are percentage, mean, and standard deviation. Test the hypothesis using t-test (Dependent Samples) The research results showed that: 1) Academic achievement after studying with electronic books combined with inquiry-based learning (5E) on the continent of Europe. Social Studies Higher than before studying with statistical significance at the .05 level. 2) Satisfaction of students who study using electronic books combined with inquiry-based learning (5E) on Europe. Social Studies It is at the highest level with an average of 4.82.